Necrotrophic fungal plant pathogens display different mechanisms to counteract grape chitinase and thaumatin-like protein. (August 2017) - Marcato, Riccardo; Sella, Luca; Lucchetta, Marco; Vincenzi, Simone; Odorizzi, Silvana; Curioni, Andrea; Favaron, Francesco
Abstract: We characterized the ability of the necrotrophic plant pathogens Botrytis cinerea, Sclerotinia sclerotiorum, Sclerotinia minor and Sclerotium rolfsii to degrade or sequester two widespread plant PR proteins: a type IV chitinase and a thaumatin-like protein (TLP). A protein (150 μg mL −1 ) extract from grape berries, containing about 58 and 68 μg mL −1 of TLP and chitinase, respectively, was added to the fungal cultures. The growth of the four fungi was not negatively affected by these proteins and, as determined by RP-HPLC, both TLP and chitinase were partially removed from the medium by the three ascomycetes fungi and almost completely by the basidiomycete S. rolfsii . Different levels of protease activity were secreted by fungi but these activities were ineffective against TLP and only partially active against chitinase. The cleavage of chitinase by B. cinerea protease generated a characteristic lower molecular size band on SDS-PAGE. To verify a possible absorption of TLP and chitinase by the fungal talli, mycelia were treated with β-1, 3-glucanase. TLP and, to a lower extent, chitinase were released from mycelium of the three ascomycetes fungi but not from that of S. rolfsii . The treatment with β-1, 3-glucanase of a mixture containing PR proteins and a purified preparation of the S. rolfsii glucan did not release TLP or chitinase. However, the two proteins were observed when the mixture was analyzed on SDS-PAGE. This result indicates a different type of binding of PR proteins with the glucan matrix of S. rolfsii in comparison to that of the three ascomycetes. As determined by RT-qPCR, one of the two examined putative glucan synthase genes of S. rolfsii was up-regulated following the administration of PR proteins, suggesting the formation of new glucan. Overall, in comparison to protease activity, the sequestering capacity of the fungal glucan matrix seems to play a major role in the fungal defense against the plant TLP and chitinase. Highlights: Four necrotrophic fungal plant pathogens differently remove grape TLP and chitinase from culture. S. rolfsii removes more TLP and chitinase compared to the ascomycetes B. cinerea, S. sclerotiorum and S. minor . Fungal proteases decrease chitinase only and B. cinerea cleaves a fragment of chitinase. TLP and chitinase are absorbed by fungal mycelia. After glucanase treatment TLP and chitinase are released from mycelium of ascomycetes but not of S. rolfsii .